It’s all in the stars: The Chinese zodiac and the effects of parental investments on offspring’s cognitive and noncognitive skill development - Tan, Chih Ming; Wang, Xiao; Zhang, Xiaobo (International Food Policy Research Institute, 2018)
The importance of (early) parental investments in children’s cognitive and noncognitive outcomes is a question of deep policy significance. However, because parental investments are arguably endogenous, it is a great challenge to empirically estimate their importance. This paper exploits a rich and novel dataset, the China Family Panel Studies, and proposes a culture-specific instrumental variable based on the Chinese zodiac, in order to address this empirical challenge. By looking at the outcomes of children born just before and just after the cutoff for a “lucky” versus “nonlucky” zodiac sign, we find that parents’ investments have significant effects on their offspring’s development of both cognitive and noncognitive skills.